What do preservice teachers learn by reflecting upon their emotional experiences during their training? A qualitative approach into four emotions. Issue 6 (2nd November 2021) - Muñoz-Salinas, Yerko; Salinas, Alvaro
ABSTRACT: Emotions and reflection are critical in teachers' work. Still, there is no agreement in how these elements connect in assessing past experiences to redesign teaching practices. In this qualitative study, we interviewed six (n = 6) Chilean preservice teachers four times each to analyse what they learn about becoming an educator by reflecting upon four emotions (anger, sadness, pride, and enjoyment). We found that teachers post-hoc reflection upon such emotions provides candidates with information to develop a sense of positional adjustment to overcome emergent difficulties at schools, reach a delimitation between the private and working world, identify teaching enhancement opportunities, and plan the incorporation of strategies in future actions. We also propose a model that coordinates suppressive and generative candidates' responses after reflecting upon their emotions. In addition, candidates perceive themselves to be unequipped to deal with their own and external emotions effectively. We suggest that emotional training should be considered as an explicit component of teacher education in Latin America.